Pengolahan Sampah Organik Menjadi Eco-Enzym Untuk Meningkatkan Ekonomi Kreatif Kelompok PKK Petukangan Jakarta Selatan - Darmawati, D. Made; Busyra, Nur; Azhar, Ervin (TAAWUN, 2023)
Turning waste into gold, something valuable for survival is determined by understanding (mindset), appreciation (internalization), and way of life (way of life) as intelligent and virtuous human beings interconnected with the environment in which we live need clean air without any waste. Environmental problems caused by piles of garbage and sources of disease that disturb the view, this can be handled properly slowly but surely, and sustainably,  Through community service with hands-on practical assistance in processing organic waste into Eco-Enzyme for group partners PKK Rw 06 Petukangan Selatan, South Jakarta.  The solution was made using the method of processing fruit and vegetable waste mixed with water and palm sugar using the ratio of organic waste: palm sugar: water = 3: 1: 10. The mixture was put in a plastic bottle or barrel, and fermented anaerobically for 3 (three) month. Eco-Enzyme is a dangerous synthetic chemical at home, by making Eco-Enzyme we can reduce the production of synthetic chemical waste from manufactured household waste. The results of the fermented Eco-Enzyme liquid can be used for various applications such as cleaning fluids for household furniture, detergents, leather cleaners, for water purification and deodorizing, for food preservation, as insecticides and pesticides, agriculture, (watering plants and improve the quality of fruit in horticulture), animal husbandry (eliminates fishy odors in the aquarium while making fish healthy), cleaning the floor of the house, for health (reaction by soaking feet in warm water mixed with Eco Enzyme, purifies the air in the room, cleanses the body, mouthwash, natural hand sanitizer.With Eco-Enzyme we have participated in reducing the burden on the earth while adopting a healthy lifestyle.